Pengaruh Budaya Organisasi SAKTI terhadap Produktivitas Pendidikan di MI Ma’arif NU Hidayatul Mubtadiin Padangasri Mojokerto - Khoirun Nasir Ma'ruf; Nersiwad; Yuliasnita Verlandes (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Organizational culture plays a very important role in determining the level of educational productivity, especially in Islamic educational institutions which have distinctive characteristics in fostering students. This study aims to determine the effect of organizational culture consisting of the SAKTI values (Salafi, Active, Creative, Taqwa, and Innovative) on educational productivity at MI Ma’arif NU Hidayatul Mubtadiin Padangasri Mojokerto. The SAKTI values are believed to create a conducive, harmonious, and motivating work environment, so that educators can work optimally in supporting the achievement of educational goals. This research employs a quantitative approach with a descriptive method. Data were collected through the distribution of questionnaires to all 32 teaching and educational staff as research respondents. Data analysis was carried out using simple linear regression with the help of the SPSS application to determine the extent of the influence of organizational culture on educational productivity. The results of the study show that the SAKTI organizational culture has a significant influence on educational productivity. This is indicated by the value of the coefficient of determination (R²) of 0.650, which means that 65% of the variation in educational productivity can be explained by organizational culture. Meanwhile, the significance value of 0.000 (p < 0.05) and the t-count of 10.211, which is greater than the t-table of 2.042, indicate that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. These findings confirm that the higher the implementation of organizational culture with SAKTI values in madrasah, the higher the level of educational productivity achieved. Therefore, Islamic educational institutions need to continuously instill, internalize, and strengthen organizational culture based on SAKTI values in order to improve the quality of educators and encourage the creation of more effective, efficient, and competitive education.